Phenomenology of Conceptual Understanding Ability, Representation, and Student Algorithm on Stoichiometry Materials - Atik Rahmawati; Ulya Lathifa; Aulia Rizki Fitriani (Journal of Educational Chemistry (JEC), 2022)
One of the basics in studying quantitative chemistry is stoichiometry. Thus, skills are needed that can support students in studying stoichiometry. The purpose of this study was to determine the level of students' conceptual understanding, representation, and algorithm skills in stoichiometric material. The subjects in this study were students of the 2019 class D Chemistry study program who had studied stoichiometry in the Basic Chemistry course I. This study was a descriptive study, had a qualitative approach, and used a phenomenological design with research techniques such as tests and interviews. The results showed that the level of students' conceptual understanding ability was 32.5% in the intuitive understanding category, 37.5% in the functional misconception category, 6.25%, in the partial understanding category, 1.25% in the correct incomplete understanding category, and 22. ,5% best understanding category. The level of student representation ability in submicroscopic phenomena was 13.53% and symbolic phenomena was 70.13%. Meanwhile, the level of students' algorithmic ability is in the unstructural category, 3.75% in the multistructural category, 43.75% in the relational category, and 0% in the extend abstract category.